Afforestation‐Related Fertilisation Quickly Turns Barren Cutaway Peatland Into a Carbon Dioxide Sink - Alexander J. V. Buzacott; Kari Laasasenaho; Risto Lauhanen; Kari Minkkinen; Paavo Ojanen; Gopal Adhikari; Liisa Jokelainen; Lassi Päkkilä; Hannu Marttila; Annalea Lohila (Global Change Biology, 2025)
Energy peat extraction has declined rapidly in Europe in recent years, leaving thousands of hectares of land requiring after‐use management and planning. A popular after‐use option, afforestation, is understudied and there is a limited understanding of its overall effect on greenhouse gas (GHG) and energy exchange. In this study, we present a multi‐year record of eddy covariance fluxes of carbon dioxide (CO 2 ), energy fluxes and surface albedo, chamber measurements of methane (CH 4 ) and (N 2 O), and estimates of lateral carbon (C) losses from dissolved organic carbon (DOC) measurements from a cutaway peatland in Finland during the first 3 years of afforestation. The site was fertilised with wood ash and 2‐year‐old Scots pine ( Pinus sylvestris ) saplings were planted. Wild vegetation emerged at the site in the first summer after fertilisation. Satellite‐derived leaf area index data showed clear year‐on‐year increases, and there was good agreement with changes in CO 2 fluxes over the full study period. The albedo of the site increased with plant cover annually, resulting in negative radiative forcings and net CO 2 ‐equivalent (CO 2 ‐eq) removals. After being a source of CO 2 in the first year (144 ± 20 g CO 2 ‐C m −2 year −1 ), the site transitioned to a sink for the next two study years (−36 ± 12 and −19 ± 19 g CO 2 ‐C m −2 year −1 ). Annual fluxes of CH 4 and N 2 O were small but not negligible. Net annual C losses stopped after 1 year, where DOC losses offset CO 2 uptake, and the afforestation resulted in a mean change in the annual net ecosystem C balance of 172 g C m −2 year −1 and radiative balance of −688 g CO 2 ‐eq m −2 year −1 over a 100‐year time horizon. Cutaway peatlands typically remain long‐term sources of C if abandoned, and our results indicate that the afforestation process can rapidly revegetate barren peatlands and halt net C losses.